Detection of CYP51A mutations in airborne Aspergillus spp isolates from intrahospital environments (2022)
ABSTRACT: Introduction: Aerobiological studies have found an increasing number of fungal taxa in the intrahospital environments, including Aspergillus species. There is a gap in knowledge on drug-susceptibility in spores circulating in intrahospital environ- ments. In this work, we evaluated the CYP51A genome alterations and Aspergillus spore susceptibility to antifungal drugs. Objectives: To determine the sequence of CYP51A gene in clinical and environmental Aspergillus spp. isolates from in- trahospital environments in Medellín, Colombia II. To evaluate the phenotypical response of Aspergillus isolates harboring mutations in CYP51 gene from intrahospital environments. Methods: We used Aspergillus spp. collected from air and surfaces from intrahospital environments, as well clinical sam- ples. We performed Whole Genome Sequencing ( WGS ) using HiSeqXten Illumina platform for species identification. Genomes were assembled de novo using the SPADES algorithm.Genome annotation by ab initio prediction was done using the Augustus program. We extracted the sequences from the CYP51A gene and its promoter using OrthoFinder workflow. To identify previ- ously described mutations related with drug-resistance, we performed SNPs search in Geneious software using Clustal Omega. For the determination of broth dilution minimum inhibitory concentrations ( MIC ) of antifungal agents, we used the Eucast method 9.4. Results: We identified 26 Aspergillus from Fumitagi section using morphological characteristics. Three were isolates from clinical samples and twenty-three were obtained from intrahospital environments. We performed whole genome sequence for identification to species level. We identified 26 Aspergillus fumigatus using an in-house script base in BLASTn algorithm for 4 genes: internal transcribed spacer, b-tubulin, calmodulin, and RNA polymerase II. OrthoFinder workflow was performed to obtain CYP51A sequence. Clustal-Omega analysis showed two SNPs A1147G and T11167A, which constituted two non- synonymous mutations N248K and I242V respectively. A total of 8 and 3 isolates presented the changes in the CYP51A gene respectively. To determine their role in antifungal resistance, the strains were tested against 10 concentrations ( 0.03-8 mg/l ) of voriconazole antifungal agent. We used one clinical isolate without genomic changes in the CYP51A gene as control. The MIC was 0.5 mg/l for all the tested isolates. This value suggests isolates are susceptible to voriconazole. Conclusions: -Identification of Aspergillus fumigatus to species level was achieved through whole genome sequence. -Described mutations had been related to resistance to voriconazole, itraconazole and had not been tested for posaconazole. In this work, isolates presenting non-synonymous mutations were susceptible to voriconazole with breakpoints > 1 mg/l. It is necessary to evaluate the antifungal susceptibility to other antifungal agents. -The mutation N248K was previously described only in isolates from clinical samples.Mutation I242V was found in clinical and environmental samples from agricultural lands. Here we described SNPs in isolates from intrahospital environments. This work is the first one describing mutations and elucidating their role in the drug-resistance of airborne A. fumigatus in Medellín, Colombia.